A long time ago in a cutting room far, far away my fifty years editing Hollywood hits - Star Wars, Carrie, Ferris Bueller's Day Off, Mission: Impossible, and more - Hirsch, Paul 1945- (Chicago Review Press, 2020)
Front cover -- Front Flip -- Title Page -- Half Title -- Copyright -- Dedication -- Contents -- Introduction -- 1. My First Hit: Carrie -- 2. Ten Years Earlier -- 3. My First Feature Film -- 4. Back to Trailers -- 5. My Next Big Break: Benny -- 6. Phantom and Its Horrors -- 7. Obsession -- 8. Star Wars -- 9. The Fury -- 10. King of the Gypsies and Home Movies -- 11. The Empire Strikes Back -- 12. Blow Out -- 13. The Black Is Back -- 14. Footloose in L.A. -- 15. Protocol -- 16. Ferris Bueller's Day Off -- 17. The Secret of My Success -- 18. Planes, Trains &amp -- Automobiles -- 19. Steel Magnolias -- 20. I Become a Studio Bigwig -- 21. Falling Down -- 22. The Trouble with Trouble -- 23. Mission: Impossible -- 24. Mighty Joe Young -- 25. Mission to Mars -- 26. Pluto Nash -- 27. Lean Times -- 28. Ray -- 29. A Fallow Stretch -- 30. Back to the Big Time -- 31. The Elder Statesman -- Postscript -- Acknowledgments -- Index -- Back Flip: About the Author -- Back Cover.
Keywords: Montage -- Film; Motion picture editors-United States-Biography; Electronic books